Q Fever awareness and risk profiles among agricultural show attendees. (11th July 2022) - Hobbs, Megan J.; Ketheesan, Natkunam; Eastwood, Keith; Massey, Peter; Ranmuthugala, Geetha; Norton, Robert; Quirk, Frances H.
Abstract: Objective: To assess awareness and risk of Q fever among agricultural show attendees. Setting: University of New England's Farm of the Future Pavilion, 2019, Sydney Royal Agricultural Show. Participants: Participants were ≥18 years, fluent in English, Australian residents, and gave their informed consent. Main Outcome Measures: Participants reported whether they had ever heard of Q fever and then completed the 'Q Tool' (www.qfevertool.com ), which was used to assess participants' demographics and risk profiles. Cross‐tabulations and logistic regression analyses were used to examine the relationship between these factors. Results: A total of 344 participants were recruited who, in general, lived in major NSW cities and were aged 40–59 years. 62% were aware of Q fever. Living in regional/remote areas and regular contact with livestock, farms, abattoirs and/or feedlots increased the likelihood of Q fever awareness. Direct or indirect contact with feral animals was not associated with Q fever awareness after controlling for the latter risk factors. 40% of participants had a high, 21% a medium, and 30% a low risk of exposure. Slightly less than 10% reported a likely existing immunity or vaccination against Q fever. Among those who were not immune, living in a regional or remote area and Q fever awareness were independently associated with increased likelihood of exposure. Conclusions: Awareness of Q fever was relatively high. Although 61% of participants had a moderate to high risk of exposure to Q fever, they had not been vaccinated. This highlights the need to explore barriers to vaccination including accessibility of providers and associated cost.